Impact of surface porosity on water flux and structural parameter in forward osmosis - Lee, Woonghee; Kang, Peter K.; Kim, Albert S.; Lee, Seockheon (ELSEVIER SCIENCE BV, 2018)
Improving water flux is a crucial objective of research in forward osmosis (FO) technology. A structural parameter is the property of the support layer of the membrane that determines the internal concentration polarization, which is determined by the bulk porosity, tortuosity, and thickness of the support layer. Surface porosity, i.e., porosity at the interface between the active and support layers, has recently been recognized as another critical factor in determining the water flux behavior and the structural parameter. In this study, the relative importance of the surface porosity, bulk porosity, and pore geometry of the support layer on water flux behavior is investigated using a recently developed pore-scale CFD simulator. To this end, various straight-like pore geometries with different combinations of surface and bulk porosities are studied. An increase in bulk porosity reduces internal concentration polarization, thereby increasing effective osmotic pressure. However, for the same magnitude of increase, an increase in surface porosity leads to a significantly larger increase in water flux. We show that water flux is most sensitive to surface porosity, and inconsistency in the structural parameter can be resolved by introducing surface porosity into the FO modeling framework.
Keywords: PRESSURE-RETARDED OSMOSIS; INTERNAL CONCENTRATION POLARIZATION; THIN-FILM COMPOSITE; POWER-GENERATION; MEMBRANE PERFORMANCE; DRINKING-WATER; TRANSPORT; DESALINATION